2021
DOI: 10.3390/polym13132116
|View full text |Cite
|
Sign up to set email alerts
|

Porous Layer-by-Layer Films Assembled Using Polyelectrolyte Blend to Control Wetting Properties

Abstract: Porous layer-by-layer (LbL) films have been employed for the implementation of superwetting surfaces, but they are limited to the LbL films consisting of only two oppositely charged polyelectrolytes. In this study, LbL films were assembled using a cationic polymer blend of branched poly(ethylene imine) (BPEI) and poly(allylamine hydrochloride) (PAH), and anionic poly(acrylic acid); they were then acid-treated at pH 1.8–2.0 to create a porous structure. The films of 100% BPEI exhibited a relatively smooth surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(77 reference statements)
0
7
0
Order By: Relevance
“… By increasing the number of layers, the thickness leveled off at six layers (Figure A) because the polymers on the surface were not assembled in regularly due to the structure with significant chain entanglements, which limited the layer to layer . Moreover, it was found that the polymer layer was thicker for CS than PEI because the relative molecular weights and space volumes of CS were greater than those of PEI Figure B shows that the thicknesses were independent of the components of GSAs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… By increasing the number of layers, the thickness leveled off at six layers (Figure A) because the polymers on the surface were not assembled in regularly due to the structure with significant chain entanglements, which limited the layer to layer . Moreover, it was found that the polymer layer was thicker for CS than PEI because the relative molecular weights and space volumes of CS were greater than those of PEI Figure B shows that the thicknesses were independent of the components of GSAs.…”
Section: Resultsmentioning
confidence: 99%
“…27 Moreover, it was found that the polymer layer was thicker for CS than PEI because the relative molecular weights and space volumes of CS were greater than those of PEI. 28 Figure 2B shows that the thicknesses were independent of the components of GSAs. Figure 2C shows that the water contact angle of the modified surface decreased by 40−70°, indicative of the enhanced hydrophilicity of the modified surfaces.…”
Section: Synthesis and Characterization Of Gsasmentioning
confidence: 92%
See 1 more Smart Citation
“…Accordingly, swelling coefficients of, respectively, up to 5-fold and 8-fold were found for PLL/HA multilayers subjected to ionic strength [ 104 ] and pH [ 105 ] stimuli. The swelling process was accompanied by structural changes in multilayer films, such as the emergence of holes in PLL/HA films when the NaCl concentration was changed from 0.15 M to 0.48 M [ 105 ] and the growth of pores in (PEI/PAH)/PAA films after the post-assembly pH was decreased to pH 2 [ 106 ]. The potential of such porous coatings was tested for designing slippery liquid-infused porous surfaces [ 106 , 107 ].…”
Section: Layer-by-layer Films and Vectors From Weak Polyelectrolytesmentioning
confidence: 99%
“…The swelling process was accompanied by structural changes in multilayer films, such as the emergence of holes in PLL/HA films when the NaCl concentration was changed from 0.15 M to 0.48 M [ 105 ] and the growth of pores in (PEI/PAH)/PAA films after the post-assembly pH was decreased to pH 2 [ 106 ]. The potential of such porous coatings was tested for designing slippery liquid-infused porous surfaces [ 106 , 107 ]. Concurrently, the modulation of the mass transport properties of weak polyelectrolyte multilayer films by post-assembly treatment has attracted much attention [ 108 ], leading to systems with tailored functions ( Table 4 ), including ionic current rectification [ 109 ], enhanced Li + conductivity [ 110 ], and filtration [ 111 ].…”
Section: Layer-by-layer Films and Vectors From Weak Polyelectrolytesmentioning
confidence: 99%